Large-lamellar Ce-based LDH material as well as preparation method and application thereof
By preparing large layers of Ce-based LDH materials, and using complexing agents and structural directing agents to control the lamellar structure, the problem of the lack of large layer structures of existing LDH materials in anti-corrosion coatings is solved, and the anti-corrosion performance of the coating is improved and effects on impedance performance.
Patent Information
- Application Number
- CN202411518409.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-21
AI Technical Summary
The existing LDH materials lack large-sheet structures in the anticorrosion coating, which is difficult to meet the needs of coating anticorrosion fillers.
By preparing a large LDH material containing CE elements, the layer structure of the complexing agent and structural -oriented agent control the material is used to form a CE base LDH material with a thickness of 30 to 100 nm and 0.3 to 5 μm diameter.
The obtained CE base LDH material has a good sheet structure, which improves the anticorrosive performance and impedance performance of the coating, and is suitable for anticorrosive coatings and anticorrosive fillers in coating.
Smart Images

Figure CN119330391A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fillers for anticorrosive coatings, and in particular relates to a large-sheet Ce-based LDH material and a preparation method and application thereof. Background Art
[0002] Anticorrosive fillers in anticorrosive coatings are important components of the coatings. They play an important role in improving the anticorrosion performance, mechanical properties and durability of the coatings. In general, inorganic fillers are the main ingredients. The mechanism of action of anticorrosive fillers is mainly the following: (1) Physical barrier effect: improving the density of the coating and blocking the corrosive medium. Anticorrosive fillers can fill the tiny pores and cracks in the coating to form a dense physical barrier. This barrier effectively blocks the direct contact between corrosive media such as water, oxygen, acid and alkali and the metal substrate, thereby slowing down or preventing the occurrence of corrosion reactions. (2) Chemical stabilization effect: resisting chemical corrosion and neutralizing corrosive substances. The anticorrosive filler itself should have good chemical stability and be able to resist the erosion of chemical media such as acids, alkalis and salts. When these chemical media try to penetrate the coating, the filler can act as a chemical barrier to slow down or prevent the occurrence of corrosion reactions. Some specific anticorrosive fillers also have the ability to neutralize corrosive substances. For example, some alkaline fillers can neutralize acidic corrosive media, thereby slowing down the corrosion rate.
[0003] Based on this, lamellar anticorrosive fillers have received a lot of attention in the business and academic circles, because the lamellar structure is not only easier to form a tight stack, but also can play a maze effect on the basis of general physical barriers, so that the corrosive medium needs to bypass multiple lamellar layers during the penetration process, thereby greatly prolonging the penetration time and improving the anticorrosion performance of the coating. Therefore, lamellar anticorrosive fillers such as glass flakes, mica flakes, metal flakes, graphene, LDH materials, etc. have been widely used. Among them, LDH materials, due to their nano-level layered structure, in addition to physical barriers and chemical barriers, can also be functionally adjusted with the help of their layered structure. For example, they can not only effectively load corrosion inhibitors, but also insert anions with corrosion inhibition into the LDH interlayer by ion exchange, thereby giving the coating excellent corrosion resistance and self-healing properties. At present, MgAl-LDH, ZnAl-LDH, CuAl-LDH and other materials have been prepared and applied in anticorrosion coatings. Based on the good performance of existing LDH materials in anticorrosion coatings, finding new LDH materials to better improve their anticorrosion effects has always been one of the directions of efforts in the industry.
[0004] At present, Ce-based passivation layer has been widely used in metal corrosion protection. It is an effective material used to replace the traditional Cr-based passivation layer to improve the corrosion resistance of materials. Its main function is to form a Ce-based protective film to isolate the metal surface from the external corrosive medium, thereby slowing down or stopping the corrosion process of the metal. Considering the passivation effect of Ce ions on the metal surface, introducing Ce elements into the lamellar LDH structure material and then using it as an anti-corrosion filler for the coating will play a triple role: (1) using the lamellar structure to play a physical shielding role; (2) in a corrosive environment, the alkaline structure of Ce-based LDH can neutralize the acidic corrosive medium, thereby slowing down the corrosion rate; (3) the released Ce ions can be used as passivation components to form a passivation layer on the metal surface, further improving the corrosion protection ability. However, only a few existing literatures have synthesized Ce-based LDH materials, and most of them are used in the field of photo / electrocatalysis, such as: Su Zhifeng. Preparation of ZnCe-LDO heterostructure catalyst and study of its photocatalytic performance [J]. Energy and Chemical Engineering, 2024, 45(01): 26-29; Another example: Jia Feihong, Guo Yuchen, Zou Xiangyu, et al. Electrocatalytic oxygen evolution behavior of Ni3S2@NiCe-LDH / NF electrode [J]. Journal of Materials Heat Treatment, 2023, 44(10): 78-86.), the synthesized LDHs are mostly rod-shaped materials, lacking large lamellar structures, and are not sufficient for coating anti-corrosion fillers. Therefore, it is necessary to develop a synthesis method for large-lamellar Ce-based LDHs to be suitable for coating anti-corrosion fillers. Summary of the invention
[0005] The main purpose of the present invention is to provide a large-sheet Ce-based LDH material and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a method for preparing a large-sheet Ce-based LDH material, which comprises: Allowing a mixed reaction system comprising at least a Ce source, a divalent metal source, a complexing agent, and a structure directing agent to react to obtain a modified metal precursor; And, an alkaline solution containing a structure directing agent is mixed with the modified metal precursor and reacted to prepare a large-sheet Ce-based LDH material.
[0007] The embodiment of the present invention further provides a large-sheet Ce-based LDH material prepared by the aforementioned preparation method. The Ce-based LDH material is a sheet material with a thickness of 30 to 100 nm and a sheet size of 0.3 to 5 μm.
[0008] The embodiment of the present invention also provides the use of the aforementioned large-sheet Ce-based LDH material in the preparation of an anti-corrosion paint or an anti-corrosion coating.
[0009] The embodiment of the present invention further provides an anti-corrosion coating, which includes the aforementioned large-sheet Ce-based LDH material as a filler.
[0010] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adopts a chelating agent and a structure-directing agent to control the formation process of the Ce-based LDH material and adjust the lamellar structure of the obtained Ce-based LDH material; firstly, the precipitation rate of the divalent metal M ions and Ce (III) ions is adjusted by the chelating agent to avoid the appearance of M(OH)2 or Ce(OH)3 structures; secondly, with the auxiliary effect of the structure-directing agent, the morphology of the synthesized Ce-based LDH material can be effectively controlled, which is helpful to obtain a Ce-based LDH material with a large lamellar structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0012] Figure 1 is a SEM image of ZnCe-LDH prepared in Example 1 of the present invention; Figure 2 is a SEM image of MgCe-LDH prepared in Example 2 of the present invention; Figure 3 is a SEM image of NiCe-LDH prepared in Example 3 of the present invention; Figure 4 is a SEM image of ZnCe-LDH prepared in Example 4 of the present invention; Figure 5 is an impedance performance diagram of the MCe-LDH material prepared in Examples 1-4 of the present invention dispersed in an epoxy coating; Figure 6 is a SEM image of the material prepared in Comparative Example 1 of the present invention; Figure 7 is a SEM image of the material prepared in Comparative Example 2 of the present invention; Figure 8 is a SEM image of the material prepared in Comparative Example 3 of the present invention; Fig. 9 is a SEM image of the material prepared in Comparative Example 4 of the present invention; Fig.10 is a SEM image of the material prepared in Comparative Example 5 of the present invention; Fig.11 is a SEM image of the material prepared in Comparative Example 7 of the present invention; Fig.12 is a SEM image of the material prepared in Comparative Example 8 of the present invention; Fig.13 It is a graph of impedance performance when the materials prepared in Example 4 and Comparative Examples 1-8 of the present invention are dispersed in an epoxy coating. DETAILED DESCRIPTION
[0013] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0014] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a large-sheet Ce-based LDH material includes: Allowing a mixed reaction system comprising at least a Ce source, a divalent metal source, a complexing agent, and a structure directing agent to react to obtain a modified metal precursor; And, an alkaline solution containing a structure directing agent is mixed with the modified metal precursor and reacted to prepare a large-sheet Ce-based LDH material.
[0015] In some preferred embodiments, the preparation method specifically includes: dispersing a Ce source and a divalent metal source in water, then adding a complexing agent and a structure directing agent at 25 to 60° C. and reacting for 0.5 to 2 hours to obtain a solution of a modified metal precursor.
[0016] Further, the Ce source includes a trivalent cerium salt, and the trivalent cerium salt includes any one or more combinations of cerium chloride, cerium chloride hydrate, cerium nitrate, cerium nitrate hydrate, cerium acetate, cerium acetate hydrate, cerium fluoride, cerium fluoride hydrate, cerium bromide, cerium bromide hydrate, cerium iodide, cerium iodide hydrate, cerium sulfate, and cerium sulfate hydrate, and is not limited thereto.
[0017] Furthermore, the divalent metal source includes any one or more combinations of Mg water-soluble compounds, Zn water-soluble compounds, and Ni water-soluble compounds, but is not limited thereto.
[0018] Furthermore, the Mg water-soluble compound includes MgCl2 and / or Mg(NO3)2, but is not limited thereto.
[0019] Furthermore, the Zn water-soluble compound includes ZnCl2 and / or Zn(NO3)2, but is not limited thereto.
[0020] Furthermore, the Ni water-soluble compound includes NiCl2 and / or Ni(NO3)2, but is not limited thereto.
[0021] Further, the complexing agent includes any one or more combinations of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetic acid, citric acid, and sodium citrate, but is not limited thereto.
[0022] Further, the structure directing agent includes polyethylene glycol (PEG) and / or polyvinyl pyrrolidone (PVP), but is not limited thereto.
[0023] Furthermore, the molar ratio of the Ce source to the divalent metal source is 1:1 to 1:3.
[0024] Furthermore, the molar ratio of the Ce source, the complexing agent and the structure directing agent is 0.3~1:0.5~3:0.00005~0.0001.
[0025] Furthermore, the alkaline solution containing a structure directing agent comprises an alkaline solution and a structure directing agent.
[0026] Furthermore, the alkaline solution includes any one or more combinations of sodium hydroxide solution, potassium hydroxide solution, and ammonium hydroxide solution, but is not limited thereto.
[0027] Furthermore, the concentration of the alkaline solution is 0.5-2 mol / L.
[0028] Furthermore, the content of the structure directing agent in the alkaline solution containing the structure directing agent is 2-10 wt %.
[0029] Furthermore, the preparation method specifically includes: adding an alkaline solution containing a structure directing agent to a solution of a modified metal precursor at a rate of 3 to 15 mL / min, and adjusting the pH value to 8 to 13, then stirring the reaction at 25 to 75°C for 6 to 48 hours, and then filtering, washing, and drying to obtain a large-sheet Ce-based LDH material.
[0030] In some more specific embodiments, the method for preparing the large-sheet Ce-based LDH material comprises: (1) Add trivalent Ce source and divalent metal (M 2+ ) source is dispersed in a water solvent in a certain proportion, a certain complexing agent and a structure directing agent are added at 25-60°C, and the reaction is carried out for 0.5-2h. After the reaction is completed, a solution of a modified metal precursor is obtained for standby use; (2) Prepare an alkaline solution of a certain concentration and add a certain structure-directing agent; (3) Slowly add the alkaline solution in step (2) to the solution of the modified metal precursor obtained in step (1), adjust the pH to 8-13, adjust the temperature to 25-75°C, stir the reaction for 6-48 hours, perform a complete precipitation reaction, filter, wash, and dry to obtain MCe-LDH sheet material, i.e., large-sheet Ce-based LDH material.
[0031] Furthermore, the obtained MCe-LDH sheet material can be further modified by intercalation, loading of corrosion inhibitors, etc., and used as an anticorrosive filler for coatings.
[0032] Preferably, the trivalent Ce source involved in the above step (1) comprises: a trivalent cerium salt soluble in an aqueous solution, such as cerium (III) chloride and its hydrates, cerium (III) nitrate and its hydrates, cerium (III) acetate and its hydrates, cerium (III) fluoride and its hydrates, cerium (III) bromide and its hydrates, cerium (III) iodide and its hydrates, cerium (III) sulfate and its hydrates, etc.
[0033] Preferably, the divalent metal (M) involved in the above step (1) 2+ ) sources include: Mg (II) water-soluble compounds (such as MgCl2, Mg(NO3)2, etc.), Zn (II) water-soluble compounds (such as ZnCl2, Zn(NO3)2, etc.), Ni (II) water-soluble compounds (such as NiCl2, Ni(NO3)2, etc.).
[0034] Preferably, the trivalent Ce source and the divalent metal (M 2+ ) source has a molar ratio of 1:1~1:3.
[0035] Preferably, the complexing agent involved in the above step (1) comprises ethylenediaminetetraacetic acid (EDTA), disodium ethylenediaminetetraacetic acid, citric acid, sodium citrate, etc.
[0036] Preferably, the structure directing agent involved in the above steps (1) and (2) comprises polyethylene glycol (PEG), polyvinyl pyrrolidone (PVP), etc.
[0037] Preferably, the alkaline solution involved in the above step (2) comprises sodium hydroxide solution, potassium hydroxide solution, ammonium hydroxide solution, etc.
[0038] Preferably, the concentration of the alkaline solution involved in the above step (2) is 0.5-2M.
[0039] Preferably, the rate of adding the alkaline solution to (1) in the above step (3) is 3-15 mL / min.
[0040] Another aspect of the embodiments of the present invention further provides a large-sheet Ce-based LDH material prepared by the aforementioned preparation method.
[0041] In some preferred embodiments, the Ce-based LDH material is a sheet material, the thickness of the Ce-based LDH material is 30-100 nm, and the sheet size is 0.3-5 μm.
[0042] Furthermore, the Ce-based LDH material has a thickness of 50 to 80 nm and a sheet diameter of 2 to 5 μm.
[0043] Another aspect of the embodiments of the present invention further provides the use of the aforementioned large-sheet Ce-based LDH material in the preparation of an anti-corrosion paint or an anti-corrosion coating.
[0044] Another aspect of an embodiment of the present invention further provides an anti-corrosion coating, which includes the aforementioned large-platelet Ce-based LDH material as a filler.
[0045] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0046] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0047] Example 1 A method for preparing a large-sheet ZnCe-LDH filler for an anti-corrosion coating comprises the following steps: (1) Disperse 0.05 mol CeCl3 and 0.05 mol ZnCl2 in 100 mL water, add 0.2 mol citric acid as a complexing agent and 1 g PVP as a structure directing agent at 50 °C, react for 1 h, and after the reaction is completed, obtain a Zn-Ce modified metal precursor solution for standby use; (2) Prepare 1 mol / L NaOH alkaline solution and add 0.5 g PVP as a directing agent; (3) The alkaline solution in step (2) is added dropwise to the Zn-Ce modified metal precursor solution obtained in step (1) at a rate of 10 mL / min, the pH is adjusted to 9, the temperature is adjusted to 45°C, the reaction is stirred for 12 hours, a complete precipitation reaction is carried out, and the ZnCe-LDH sheet material is obtained after filtering, washing, and drying.
[0048] The morphology of the ZnCe-LDH sheet material prepared in this example is as follows Figure 1 As shown in the SEM image.
[0049] Example 2 A method for preparing a large-layer MgCe-LDH filler for an anti-corrosion coating comprises the following steps: (1) Disperse 0.03 mol CeCl3 precursor and 0.09 mol ZnCl2 precursor into 150 mL water, add 0.5 mol citric acid as a complexing agent and 2 g PVP as a structure directing agent at 60 °C, react for 1 h, and after the reaction is completed, obtain a Zn-Ce modified metal precursor solution for standby use; (2) Prepare 1 mol / L NH4OH alkaline solution and add 1 g PVP as a directing agent; (3) The alkaline solution in step (2) is added dropwise to the Mg-Ce modified metal precursor solution obtained in step (1) at a rate of 15 mL / min, the pH is adjusted to 13, the temperature is adjusted to 60°C, the reaction is stirred for 36 hours, a complete precipitation reaction is carried out, and the MgCe-LDH sheet material is obtained after filtering, washing, and drying.
[0050] The morphology of the MgCe-LDH sheet material prepared in this example is as follows Figure 2 As shown in the SEM image.
[0051] Example 3 A method for preparing a large-layer NiCe-LDH filler for an anti-corrosion coating comprises the following steps: (1) Disperse 0.04 mol CeCl3 and 0.08 mol NiCl2 in 120 mL water, add 0.3 mol citric acid as a complexing agent and 1 g PVP as a structure directing agent at 50 °C, react for 2 h, and after the reaction is completed, obtain a Ni-Ce modified metal precursor solution for standby use; (2) Prepare 1 mol / L NaOH alkaline solution and add 0.5 g PVP as a structure-directing agent; (3) The alkaline solution in step (2) is added dropwise to the Ni-Ce modified metal precursor solution obtained in step (1) at a rate of 5 mL / min, the pH is adjusted to 10, the temperature is adjusted to 75°C, the reaction is stirred for 12 hours, a complete precipitation reaction is carried out, and the NiCe-LDH sheet material is obtained after filtering, washing, and drying.
[0052] The morphology of the NiCe-LDH sheet material prepared in this example is as follows Figure 3 As shown in the SEM image.
[0053] Example 4 A method for preparing a large-sheet ZnCe-LDH filler for an anti-corrosion coating comprises the following steps: (1) Disperse 0.03 mol Ce(NO3)3 and 0.06 mol Zn(NO3)2 in 100 mL water, add 0.3 mol EDTA as a complexing agent and 0.5 g PVP as a structure directing agent at 60 °C, react for 2 h, and after the reaction is completed, obtain a Zn-Ce modified metal precursor solution for standby use; (2) Prepare 1 mol / L KOH alkaline solution and add 0.5 g PVP as a directing agent; (3) The alkaline solution in step (2) is added dropwise to the Zn-Ce modified metal precursor solution obtained in step (1) at a rate of 10 mL / min, the pH is adjusted to 11, the temperature is adjusted to 60°C, the reaction is stirred for 24 hours, a complete precipitation reaction is carried out, and the ZnCe-LDH sheet material is obtained after filtering, washing, and drying.
[0054] The morphology of the ZnCe-LDH sheet material prepared in this example is as follows Figure 4 As shown in the SEM image in the middle, the thickness is 50 to 80 nm and the flake size is 2 to 5 μm.
[0055] Comparative Example 1 The method is the same as Example 4, except that: in step (1), there is no complexing agent. The morphology of the material in this comparative example is as follows: Figure 6 shown.
[0056] Comparative Example 2 The method is the same as Example 4, except that: in step (1), there is no structure directing agent. The morphology of the material in this comparative example is as follows: Figure 7 shown.
[0057] Comparative Example 3 The method is the same as Example 4, except that: in step (2), there is no structure directing agent. The morphology of the material in this comparative example is as follows: Figure 8 shown.
[0058] Comparative Example 4 The method is the same as Example 4, except that the dropping speed in step (3) is 20 mL / min. The morphology of the material in this comparative example is as follows: Fig. 9 shown.
[0059] Comparative Example 5 The method is the same as Example 4, except that: the pH value in step (3) is 7, and the morphology of the material in this comparative example is as follows: Fig.10 shown.
[0060] Comparative Example 6 The method is the same as Example 4, except that the pH value in step (3) is 14, but the pH in this experiment cannot reach pH 14, so the preparation cannot be carried out.
[0061] Comparative Example 7 The method is the same as Example 4, except that the temperature in step (3) is 90°C. The morphology of the material in this comparative example is as follows: Fig.11 shown.
[0062] Comparative Example 8 The method is the same as Example 4, except that the temperature in step (3) is 4°C. The morphology of the material in this comparative example is as follows: Fig.12 shown.
[0063] Application examples: The MCe-LDH materials prepared in Examples 1-4 were dispersed into epoxy coatings to test their impedance properties. The impedance properties of the coatings were as follows: Figure 5 As shown, the large sheet structure obtained in Examples 3 and 4 exhibits better coating impedance. The materials prepared in Example 4 and Comparative Examples 1-8 were dispersed into epoxy coatings to test their impedance properties. The coating impedance properties are shown in FIG. Fig.13 shown.
[0064] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0065] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a large-sheet Ce-based LDH material, characterized in that: include: Allowing a mixed reaction system comprising at least a Ce source, a divalent metal source, a complexing agent, and a structure directing agent to react to obtain a modified metal precursor; And, an alkaline solution containing a structure directing agent is mixed with the modified metal precursor and reacted to prepare a large-sheet Ce-based LDH material.
2. The preparation method according to claim 1, characterized in that: Specifically include: The Ce source and the divalent metal source are dispersed in water, and then a complexing agent and a structure directing agent are added at 25 to 60° C. and reacted for 0.5 to 2 hours to obtain a solution of a modified metal precursor.
3. The preparation method according to claim 2, characterized in that: The Ce source includes a trivalent cerium salt, and the trivalent cerium salt includes any one or more combinations of cerium chloride, cerium chloride hydrate, cerium nitrate, cerium nitrate hydrate, cerium acetate, cerium acetate hydrate, cerium fluoride, cerium fluoride hydrate, cerium bromide, cerium bromide hydrate, cerium iodide, cerium iodide hydrate, cerium sulfate, and cerium sulfate hydrate; And / or, the divalent metal source includes any one or more combinations of Mg water-soluble compounds, Zn water-soluble compounds, and Ni water-soluble compounds; preferably, the Mg water-soluble compound includes MgCl2 and / or Mg(NO3)2; preferably, the Zn water-soluble compound includes ZnCl2 and / or Zn(NO3)2; preferably, the Ni water-soluble compound includes NiCl2 and / or Ni(NO3)2; And / or, the complexing agent includes any one or more combinations of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetic acid, citric acid, and sodium citrate; And / or, the structure directing agent comprises polyethylene glycol and / or polyvinyl pyrrolidone.
4. The preparation method according to claim 2, characterized in that: The molar ratio of the Ce source to the divalent metal source is 1:1 to 1:3; And / or, the molar ratio of the Ce source, the complexing agent and the structure directing agent is 0.3~1:0.5~3:0.00005~0.0001.
5. The preparation method according to claim 1, characterized in that: The alkaline solution containing a structure directing agent comprises an alkaline solution and a structure directing agent; Preferably, the alkaline solution comprises any one or more combinations of sodium hydroxide solution, potassium hydroxide solution and ammonium hydroxide solution; preferably, the concentration of the alkaline solution is 0.5-2 mol / L; preferably, the content of the structure directing agent in the alkaline solution containing the structure directing agent is 2-10 wt%.
6. The preparation method according to claim 2, characterized in that: Specifically include: An alkaline solution containing a structure directing agent is added to a solution of a modified metal precursor at a rate of 3 to 15 mL / min, and the pH value is adjusted to 8 to 13. The mixture is stirred and reacted at 25 to 75° C. for 6 to 48 hours. The mixture is then filtered, washed, and dried to obtain a large-sheet Ce-based LDH material.
7. The large-sheet Ce-based LDH material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The Ce-based LDH material is a sheet material with a thickness of 30 to 100 nm and a sheet diameter of 0.3 to 5 μm.
8. The Ce-based LDH material according to claim 7, characterized in that: The thickness of the Ce-based LDH material is 50-80 nm, and the sheet diameter is 2-5 μm.
9. Use of the large-sheet Ce-based LDH material according to claim 7 or 8 in the preparation of anti-corrosion paint or anti-corrosion coating.
10. An anticorrosive coating, characterized in that: A Ce-based LDH material comprising a large sheet as claimed in claim 7 or 8 as a filler.